Patient function, long‐term survival, and use of surgery in patients with kidney cancer. Issue 24 (12th August 2016) - Tan, Hung‐Jui; Chamie, Karim; Daskivich, Timothy J.; Litwin, Mark S.; Hu, Jim C.
Abstract : BACKGROUND: Beyond age and comorbidity, functionality can shape the long‐term survival potential of patients with cancer. Accordingly, herein the authors compared mortality and receipt of cancer‐directed surgery according to patient function among older adults with kidney cancer. METHODS: Using Surveillance, Epidemiology, and End Results (SEER)‐Medicare data from 2000 through 2009, the authors studied 28, 326 elderly subjects with primary kidney cancer. Patient function was quantified using function‐related indicators, claims indicative of dysfunction and disability. Adjusting for patient and cancer characteristics, competing risk regression was used to assess the relationship between function‐related indicator count and cause‐specific mortality and then generalized estimating equations were used to quantify the probability of surgery. RESULTS: A total of 13, 619 adult patients (48.1%) with at least 1 function‐related indicator were identified. A higher indicator category was associated with older age, greater comorbidity, female sex, unmarried status, lower socioeconomic status, and higher stage of disease ( P <.001). Compared with patients with an indicator count of 0, those with an indicator count of 1 (hazard ratio, 1.10; 95% confidence interval [95% CI], 1.04‐1.16) and ≥2 (hazard ratio, 1.46; 95% CI, 1.39‐1.53) were found to have higher other‐cause mortality. Conversely, kidney cancer mortality varied minimally with patient function. Patients with ≥ 2 indicators received cancer‐directed surgery less often than those without disability (odds ratio, 0.61; 95% CI, 0.56‐0.66), although treatment probabilities remained high for patients with locoregional disease and low for those with metastatic cancer. CONCLUSIONS: Among older adults with kidney cancer, functional health stands as a significant predictor of long‐term survival. However, receipt of cancer‐directed surgery appears largely determined by cancer stage. Patient function should be considered more heavily when determining treatment for older adults with kidney cancer. Cancer 2016;122:3776–3784. © 2016 American Cancer Society. Abstract : In addition to age and comorbidity, patient function impacts the long‐term survival of adults with kidney cancer. Although baseline disability influences treatment use to a modest degree, receipt of surgery varies mostly with cancer stage, thereby underscoring the need to more meaningfully consider functionality in the management of patients with cancer of the kidney.